Direct Fluoro‐aminosulfenylation of Active Methylenes by Dialkylaminosulfur Trifluorides under Catalyst‐Free Conditions. Issue 10 (13th July 2016) - Saidalimu, Ibrayim; Guo, Ming; Tokunaga, Etsuko; Shibata, Norio
Abstract: The direct fluoro–aminosulfenylation of active methylene compounds by diethylaminosulfur trifluoride (DAST) and its derivatives is disclosed. A variety of α ‐fluorinated α ‐sulfenamides with a tetrasubstituted carbon center were synthesized from β‐keto esters, malonates, 1, 3‐diketones, and dicyanoalkylidenes under mild reaction conditions. This direct fluoro–aminosulfenylation reaction occurs very smoothly under metal‐free and base‐free conditions. Abstract : DASTer Plan : The direct fluoro‐aminosulfenylation reaction of active methylene compounds using diethylaminosulfur trifluoride (DAST) to afford α‐fluoro‐α‐aminosulfenyl compounds with a tetrasubstituted carbon center in high yields has been developed. The methylene compounds, including β‐keto esters, malonates, 1, 3‐diketones, and dicyanoalkylidenes, reacted with DAST under the same reaction conditions to furnish α‐fluoro‐α‐diethylaminosulfenyl compounds.